Pengaruh Edukasi Gizi terhadap Praktik Pemberian Makan Pada Baduta Stunting di Kabupaten Bengkulu Utara - Agus Sri Banowo; Yance Hidayat (Universitas Batanghari Jambi, 2021)
Stunting is a less chronic nutritional problem. The practice of feeding is one of the factors that contribute to stunting, so there is a need for nutrition education regarding the practice of providing food. This study aims to discuss nutrition education interventions on the practice of feeding mothers who have stunting. The study design used a quasi-experimental design with a pre-posttest design of two groups. The research location was Kerkap health centre as an intervention and Air Lais health centre as a control with a sample of 40 people each. The test used in this study paired-sample t-test and independent t-test. The different tests' results depend on the average meal management between the control groups and comparison with p values of 0,000 and 0.168, and independent tests between the intervention group and the control group of 0,000. Nutrition education is a particular program to improve the practice of family feeding of stunting children.